Are the review criteria for automated complete blood counts of the International Society of Laboratory Hematology suitable for all hematology laboratories? - Comar,Samuel Ricardo (2014)
OBJECTIVE: to verify whether the review criteria for automated blood counts suggested by the International Consensus Group for Hematology Review of the International Society for Laboratory Hematology are suitable for the Hematology Laboratory of Hospital de Clinicas, Universidade Federal do Paraná.METHODS: initially, the review criteria of the International Society for Laboratory Hematology were adapted due to limitations in the Institution's electronic hospital records and interfacing systems. The adapted review criteria were tested using 1977 samples. After this first assessment, an additional 180 inpatient samples were analyzed to evaluate the screening criteria of the review criteria in conjunction with positive smear findings established by the institution. The performance of the review criteria was verified by determining false positive, false negative, true positive and true negative rates, sensitivity, specificity, positive predictive value, negative predictive value, microscopic review rate and efficiency.RESULTS: initial analysis showed false negatives = 6.73%, false positives = 23.27%, microscopic review rate = 46.03% and efficiency = 70.0%. An evaluation of the screening criteria adapted from the review criteria together with the positive smear findings of the institution showed false negatives = 15.5%, false positives = 10.5%, microscopic review rate = 37.3% and efficiency = 73.8%. In both situations the safety limit (false negative <5%) recommended by the review criteria was exceeded.CONCLUSIONS: the review criteria adapted from the International Society for Laboratory Hematology are neither suitable nor safe for use in the hematology laboratory of the Hospital de Clinicas. This implies a need to develop and validate institution-specific review criteria in order to decrease false negative results to an acceptable and safe rate for patients.